Modernistic Views on Catholicism in the Works by A. Maceina and P. Jakas - Pruskus, Valdas (Problemos, 1983)
The attempts by A. Maceina (b. 1908) and P. Jakas (1908-1968), Lithuanian Catholic modernists, to critically evaluate Catholicism in bourgeois Lithuania and reveal its possible renovation are considered. The latter is understood by them as not only a democratization of clerical .institutions, the rites of pastoral activities (P. Jakas), but also as an intensification of spiritual component in faith (A. Maceina), which is found to be the way to believers. They both were striving to resist secularization of society and, at the same time, pursuing a more flexible defence of Catholic religion and’ the interests of Church.